Cytokine profile in peripheral blood mononuclear cells differs between embryo donor and potential recipient sows - Cambra, Josep M.; Gil, Maria A.; Cuello, Cristina; Gonzalez-Plaza, Alejandro; Rodriguez-Martinez, Heriberto; Klymiuk, Nikolai; Martinez, Emilio A.; Parrilla, Inmaculada (Frontiers in Veterinary Science, 2024)
Introduction Pregnancy success relies on the establishment of a delicate immune balance that requires the early activation of a series of local and systemic immune mechanisms. The changes in the immunological profile that are normally occurring in the pregnant uterus does not take place in cyclic (non-pregnant) uterus, a fact that has been widely explored in pigs at the tissue local level. Such differences would be especially important in the context of embryo transfer (ET), where a growing body of literature indicates that immunological differences at the uterine level between donors and recipients may significantly impact embryonic mortality. However, whether components of peripheral immunity also play a role in this context remains unknown. Accordingly, our hypothesis is that the immune status of donor sows differs from potential recipients, not only at the tissue local level but also at the systemic level. These differences could contribute to the high embryonic mortality rates occurring in ET programs. Methods In this study differences in systemic immunity, based on cytokine gene expression profile in peripheral blood mononuclear cells (PBMCs), between embryo-bearing donor (DO group; N = 10) and potential recipient sows (RE group; N = 10) at Day 6 after the onset of the estrus were explored. Gene expression analysis was conducted for 6 proinflammatory (IL-1α, IL-1β, IL-2, GM-CSF, IFN-γ, and TNF-α) and 6 anti-inflammatory (IL-4, IL-6, IL-10, IL-13, TGF-β1, and LIF) cytokines. Results and discussion All cytokines were overexpressed in the DO group except for IL-4, suggesting that stimuli derived from the insemination and/or the resultant embryos modify the systemic immune profile in DO sows compared to RE (lacking these stimuli). Our results also suggest that certain cytokines (e.g., IL-1α and IL-1β) might have a predictive value for the pregnancy status.